Livestock grazing affects microclimate conditions for decomposition process through changes in vegetation structure in mountain grasslands - Vaieretti, Maria Victoria (2018)
It is often assumed that a change in litter quality is the main driver of alterations in the decomposition process when grazers modify vegetation structure. Soil microclimate is also modified, but this driver of decomposition has been far less studied than litter quality. We analyzed the relationships among vegetation structure, microclimate and decomposition in different mountain grassland types, across a fence-line separating paddocks with different grazing intensity. Along the fence, we selected nine pairs of contrasting grassland types including lawns and tall tussock grasslands, which are associated with high and low local grazing pressure, respectively. At each site (N = 18) we estimated growth form composition and vegetation height. During the growing season we recorded soil temperature, soil moisture and the photosynthetically active radiation. Within the same period, we measured the decomposition rate of two common litter substrates. We analyzed the relationships among those variables at the landscape and at the local scale. At the landscape scale we considered the variation across all sites (N = 18). At the local scale we considered each pair as a sample (N = 9) and the differences between both sides of the fence as the variables to correlate. Our results indicate that when short grasslands are released from grazing and tall grasslands became dominant, temperature and light at the soil level are reduced, while soil moisture tends to increase, enhancing decomposition. Furthermore, these results show that the microclimatic conditions effect can counteract the litter quality effect (reported in previous studies) on decomposition, resulting in increased decomposition rates when grazing is reduced.